Conceptualising post-stroke fatigue: a cross-sectional survey of UK-based physiotherapists and occupational therapists. Issue 12 (10th December 2019) - Thomas, Karen; Hjalmarsson, Clarissa; Mullis, Ricky; Mant, Jonathan
Abstract : With survival after stroke improving, more people are discharged into the community with multiple and persistent deficits. Fatigue is a common unmet need for stroke survivors, but there are no evidence-based guidelines for its assessment and management. This study explored how UK-based therapists conceptualise post-stroke fatigue (PSF) in current practice. Objective: To describe current understanding of PSF among physiotherapists (PT) and occupational therapists (OT). Design: A cross-sectional online survey using Qualtrics software (a survey creation and analysis programme) was sent to therapists working with stroke survivors in 2019. Responses to the open ended question, 'How would you describe PSF if approached by another healthcare professional?' were analysed thematically by two independent researchers. Participants: 137 survey respondents (71 PT and 66 OT) from a range of clinical settings (25 acute care, 24 sub-acute rehabilitation care, 3 primary care and 85 community care) with 7 months-36 years of experience working with stroke survivors completed the survey. Results: Respondents stated that PSF should be regarded as an important medical condition because it is common and can be associated with severe symptoms. Symptoms were perceived to be highly variable and the syndrome was difficult to define objectively. It was felt to have both physical and cognitive components. A variety of different opinions were expressed with regard to causation, conceptualisation and best management. Conclusion: Therapists working with stroke survivors conceptualise and manage PSF in different ways. Clinical practice is hampered by a lack of a widely adopted definition, and a small evidence base. Research into causes and management of PSF is a priority.